The case for integrated pest management in Africa: transition from a pesticide-based approach - Srinivasan, R.; Tamò, Manuele; Subramanian, S. (Elsevier, 2022)
Pest management in major cropping systems has long been dominated by chemical pesticides in Africa. Smallholder farmers have perceived pesticides as insurance to protect their crops. Consumers are less aware of pesticide-related food-safety issues, and markets providing economic incentives to producers who adopt alternatives to pesticides have been slow to emerge. Hence, overuse of pesticides has been constantly increasing. Although African countries have a number of pesticide-related policies, they are inadequately implemented. However, significant investment has been made on integrated pest management (IPM) innovations in recent decades. Resistant cultivars, agroecological approaches, biological control, and biopesticides have been developed against key biotic constraints in major cropping systems. They have been adopted at several pilot sites, where significant economic and ecological impacts have been documented. However, concerted efforts are necessary to harmonize policies and regulations across the continent to enhance the availability, accessibility, and affordability of IPM innovations to smallholder farmers.